Implementation of Problem Financing Risk Control Strategy on Amanah Products at PT. Luwu Branch Sharia Pawntown - Indah Sari (Program Studi Perbankan Syariah, IAIN Palopo, 2022)
This thesis discusses the risk control strategy for non-performing financing on trust products at PT. Luwu Branch Sharia Pawnshop. This study aims to describe the strategy of PT. Sharia Pegadaian Luwu Branch in risk control on trustful products. The type of research used is qualitative research with a descriptive approach. Data obtained by conducting observations, interviews and documentation. The results showed that the risk control strategy of PT. Sharia Pegadaian Luwu Branch for non-performing financing has been implemented, especially for Amanah products. This strategy includes risk monitoring, risk measurement, risk monitoring, and financing problem solving. In identifying the financing risks of PT. Luwu Branch Sharia Pegadaian uses 5C analysis and BI verification. For risk measurement, PT. Pegadaian Syariah Luwu Branch uses quantitative and qualitative risk measurements and divides them into five categories, namely current, substandard, on special mention, doubtful, and loss. In monitoring the risk of financing PT. The Luwu Branch Sharia Pawnshop made the first visit to the customer’s location, but follow-up was not carried out properly after the disbursement of the financing. Meanwhile, for the settlement of non-performing financing, PT. The Luwu Branch of Sharia Pegadaian contacts customers, visits customers and shows a letter of repayment.